RADIKALISME ISLAM KONTEMPORER DAN MINDSET KEAGAMAAN KAUM KHAWARIJ - Hanik Yuni Alfiyah; Muhammad Fahmi; Saefullah Azhari; Sutikno Sutikno; Senata Adi Prasetia (Tasyri’: Jurnal Tarbiyah – Syari’ah Islamiyah, 2026)
This article departs from the contemporary phenomenon of Islamic radicalism, which frequently manifests in patterns of exclusivism, claims of absolute truth, and the practice of takfir toward other groups. This phenomenon indicates a resemblance to the historical mindset of the Khawarij, particularly in their literal and rigid interpretation of religious texts. The main problem addressed in this study concerns the extent to which the Khawarij mindset remains relevant in shaping contemporary Islamic radicalism, as well as how such patterns are reproduced within current socio-religious contexts. This study aims to analyze the relationship between the construction of Khawarij thought and the expressions of contemporary radicalism, while also identifying the factors that drive the reproduction of these patterns. The research employs a library research method, utilizing a conceptual analytical approach to examine relevant classical and contemporary literature. The findings reveal an epistemological continuity between the Khawarij mindset and certain contemporary radical movements, particularly in terms of narrow textual interpretation, the delegitimization of moderate religious authorities, and the justification of violence in the name of religion. However, in the contemporary context, these patterns are further reinforced by socio-political factors, digital media, and identity crises. The implications of this study highlight the importance of strengthening contextual religious literacy, developing inclusive approaches in Islamic education, and formulating deradicalization strategies grounded in historical and sociological understanding. Such efforts are expected to reduce the reproduction of exclusive mindsets and promote a more moderate and dialogical form of religious expression in the future.